REKONSTRUKSI AKUNTANSI SEKTOR PUBLIK DI PEMERINTAHAN TINGKAT RT/RW - Widarno, Bambang -; -, Suharno - (Eksplorasi, 2008)
Abstract Governance in level of RT/RW represent level of lowest governance at one blow as back part harpoon from grand system of governance of exist in Indonesia. Pattern of Management system of good governance have righteously reach system of governance in level of RT/RW of according to reform trust. Problem of RT/RW do not limited to the hygiene problem, work to devote, security, social and the other classic problem. But there is dissimilar problem which during the time not yet got good attention and serious the than manager RT/RW, governmental, and also citizen of meaning will be important of management of better administration with applying of accountancy of RT/RW to increase quality of presentation of finance information. Applying of accountancy in level of RT/RW conducted to increase accountability, function manajerial, transparency, and balance usher generation. Although Standard of Accountancy of Governance only arrange in level of central government and also area, but accountancy RT/RW remain to be applicable according to principle accepted by a public although with a few the exemption. Accountancy of RT/RW made by more simple remember ability of accountancy of citizen of society which relative lower. Payes manager of low RT/RW and lack of support from area Government can become constraint in applying of accountancy RT/RW, for that require to be done by a more wise approach and strategy how accountancy of enforceable RT/RW better. Financial statement of RT/RW consisted of by Balance sheet of RT/RW and Cash flow statement; therewith enlist its supporter like: Daily Cashbook, Enlist Supply, Enlist Plant Asset, Enlist Citizen Deposit, Enlist Citizen Loan, Card of Saving and lending Citizen, and Enlist Contribution Giver. Keyword: Standard of Governance Accountancy, Accountancy RT/RW, Balance Sheet of RT/RW and Cash flow statement, Daily Cashbook, Enlist Supply, Enlist Plant Asset, Enlist Citizen Deposit, Enlist Citizen Loan, Card of Saving and lending Citizen, and Enlist Contribution Giver.